Novel insights into dendritic cells in the pathogenesis of systemic sclerosis. (13th February 2020) - Carvalheiro, T.; Zimmermann, M.; Radstake, T. R. D. J.; Marut, W.
Summary: Systemic sclerosis (SSc) is a severe autoimmune fibrotic disease characterized by fibrosis, vasculopathy, and immune dysregulation. Dendritic cells (DCs) are the most potent antigen‐presenting cells, specialized in pathogen sensing, with high capacity to shape the immune responses. The most recent technological advances have allowed the discovery of new DC subsets with potential implications in inflammatory conditions. Alterations of DC distribution in circulation and affected tissue as well as impaired DC function have been described in SSc patients, pointing towards a crucial role of these cells in SSc pathogenesis. In particular, recent studies have shown the importance of plasmacytoid DCs either by their high capacity to produce type I interferon or other inflammatory mediators implicated in SSc pathology, such as chemokine C‐X‐C motif ligand 4 (CXCL4). In‐vivo models of SSc have been vital to clarify the implications of DCs in this disease, especially DCs depletion and specific gene knock‐down studies. This review provides these new insights into the contribution of the different DCs subsets in the pathogenesis of SSc, as well as to the novel developments on DCs in in‐vivo models of SSc and the potential use of DCs and their mediators as therapeutic targets. Abstract : Dendritic cells play a crucial role in the pathogenesis of systemic sclerosis. Herein, we summarized very recent findings on the role of classical, plasmacytoid and monocyte‐derived inflammatory dendritic cells, in both, human and mouse studies in the disease. Furthermore, we discussed current and potential treatment options targeting dendritic cells function in systemic sclerosis.